Constitutive expression of the oat arginine decarboxylase cDNA in transgenic wheat plants does not influence expression of its orthologue - Bassie L.; Peremarti A.; Zhu C.; Christou P.; Capell T. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The Polyamines (PAs) putrescine (Put), spermidine (Spm) and spermine (Spm) play vital roles in the growth and development of all living organisms. Elevated amounts of PAs, especially Put, appear to be important in the physiological response of plants exposed to various stresses such as potassium deficiency, acidic soils, environmental pollutants, temperature and drought. We reported previously, that over-expression of the Datura stramonium arginine decarboxylase (adc) cDNA conferred tolerance in transgenic rice plants when these were subjected to drought stress. We subsequently generated a wheat population expressing the oat adc cDNA. We investigated spatial and temporal expression of the transgene and the endogenous gene at the mRNA level. Transcript and polyamine profiles were correlated. This homozygous transgenic wheat population is currently being used for further abiotic stress experiments.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)